The influence of dietary conditions in the effects of resveratrol on hepatic steatosis. Issue 11 (4th November 2020) - Milton-Laskibar, I.; Aguirre, L.; Gómez-Zorita, S.; Rolo, A. P.; Portillo, M. P.
Abstract : Non-alcoholic fatty liver disease (NAFLD) is considered the major cause for the development of chronic liver alterations. Abstract : Non-alcoholic fatty liver disease (NAFLD) is considered the major cause for the development of chronic liver alterations. Hepatic steatosis is the most benign and common form of NAFLD, although its potential to evolve into more detrimental liver alterations makes its treatment necessary. In this regard, much attention has been paid to polyphenols, with resveratrol being one of the most studied ones. This review is aimed at studying the effects induced by resveratrol on hepatic steatosis in both preclinical studies conducted under different feeding conditions (overfeeding, normal feeding and caloric restriction), and in clinical trials. The vast majority of studies have been conducted by administering the polyphenol at the same time as an obesogenic diet. Under these experimental conditions, resveratrol has shown effectiveness improving diet-induced excessive liver lipid accumulation. Data are scarce for studies carried out by administering resveratrol under standard or energy-restricted feeding conditions. In this regard, while resveratrol retains its effectiveness, ameliorating hepatic steatosis under standard feeding conditions, such an effect has not been reported for the administration of the polyphenol under energy restriction. With regard to clinical trials, in the majority of them, resveratrol did not show its effectiveness in improving hepatic steatosis. This lack of effect could be due to significant differences in the experimental procedures (mainly the length of the experimental period). The relevance of liver fat content at the baseline should also be considered. Altogether, there is no sufficient scientific support so far for proposing resveratrol as a tool for hepatic steatosis treatment.